General Lee's resignation : To the Right Honourable Lord Viscount Barrington, His Majesty's secretary at war. Philadelphia, June 22, 1775. My Lord, although I can by no means subscribe to the opinion of divers people in the world, that an officer on half pay is to be considered in the service, yet I think it a point of delicacy to pay a deference to this opinion, erroneous and absurd as it is. I therefore apprise your lordship in the most public and solemn manner, that I renounce my half-pay, from the date hereof . - Lee, Charles, 1731-1782 (LLMC-digital (Series), 1775)
Publicly declining to support the British cause.